Distant lung metastases caused by a histologically benign phosphaturic mesenchymal tumor. (16th May 2018) - Yavropoulou, Maria P; Poulios, Christos; Foroulis, Christoforos; Tournis, Symeon; Hytiroglou, Prodromos; Kotsa, Kalliopi; Kessisoglou, Isaak; Zebekakis, Pantelis
Summary: Tumor-induced osteomalacia (TIO) is a rare form of hypophosphatemia usually caused by phosphaturic mesenchymal tumors (PMTs); the biologic behavior of PMTs is under investigation. Herein we present a case of TIO with a protracted course over 12 years leading to a fatal outcome. A 39-year-old man presented with weakness in 2004 and was found to have decreased serum phosphorus, phosphaturia and low levels of 1, 25-dihydroxyvitamin D3. Four years later he developed a painful left calf mass. The lesion was resected, but recurred causing extreme pain and dysfunction. Radiological examination showed a large cluster of soft tissue tumors affecting all the muscle compartments of the calf and a smaller lesion inside the metaphysis of the tibia. Above-knee amputation was performed. Histological examination of all lesions showed a cellular spindle cell neoplasm with variously sized vessels, wide vessel-like spaces and scattered deposits of calcified extracellular material. The tumor infiltrated skeletal muscles, subcutaneous fat and the proximal end of the fibula. The tibial lesion had identical histology. Three years after the amputation the patient presented with cough and dyspnea. Radiological examination, followed by an open biopsy, showed that there were multiple metastatic nodules of PMTs in both lungs. Shortly after the diagnosis the patient died. This case illustrates that even benign cases of PMTs may lead to a fatal outcome and the classification of PMTs into benign and malignant should be reassessed in order to correspond to its biological behavior. Learning points: PMTs, aside from having locally aggressive behavior, may metastasize and cause death PMTs may behave aggressively despite 'benign' histological findings Accurate diagnosis of tumor-induced osteomalacia and patient management require a multidisciplinary approach